Energy-Economy-Ecology-Engineering (4E) Integrated Approach for GHG Inventories - UYAR, TANAY SIDKI (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
Energy is the main driver of modern national economies. However, energy systems are highly complex and obtaining energy-efficient and clean solutions at the lowest cost is becoming harder under these dynamic circumstances. An integrated decision-making tool is needed in these circumstances as a compass for decision makers. This study aimed to create such a model for Turkey, spanning the period 2005-2025. Firstly, energy supply commodities, sectors and sectoral demands, conversion and process technologies, consumption and demand technologies are determined for Turkey based on energy balance statistics published by the Ministry of Energy and Natural Resources. This database is called the Reference Energy System, and included parameters characterizing each of the technologies and resources used to obtain the energy equilibrium, including fixed and variable costs, technology availability, performance and pollutant emissions. The model also allows user-defined variables. After developing alternative scenarios to achieve cost-effective technology selection and running each alternative of the base scenario one by one, model responses and scenario results are analyzed to provide technical recommendations. Therefore, a functional 'energy-economy-ecology-engineering' integrated model calculating final energy consumption from primary energy supply was developed with optimal solutions including both current energy technologies and candidates for near future utilization.
Keywords: ETSAP; Turkish model; Greenhouse gases (GHGs); GHG emissions estimation; EMISSIONS; TARGETS; IMPACTS